The Failed Conversion of CareFirst BlueCross BlueShield to For-Profit Status: Part 2, Lessons Learned - Bruce McPherson (SAGE Publishing, 2004)
This article presents lessons for other states and all types of nonprofit health care organizations from the failure by nonprofit CareFirst Blue Cross Blue Shield to convert to for-profit status and be sold to the publicly traded Wellpoint Health Networks, Inc. The lessons relate only in part to conversions. More broadly they concern any kind of strategic decision making by nonprofit health care boards of directors and their executives that substantially affects the public interest. This article is a companion to one by this same author published in the Fall 2004 issue of Inquiry. That article chronicled the events and political environment surrounding the conversion proposal, the review process and decision, and the aftermath of actions and reactions by various parties, including state legislation to clarify CareFirst's mission and to reform its board.